EFEKTIVITAS PEMBELAJARAN MATEMATIKA MENGGUNAKAN SISTEM DARING - AMINULLAH AMINULLAH (Universitas Mahasaraswati Mataram, 2021)
Learning or lectures that have to be carried out with an online system after the Covid-19 have surprised universities and students who are particularly underdeveloped in the field of science and technology. The purpose of this study is to describe the effectiveness of learning mathematics using an online system. The research design used was Classroom Action Research with the Kemmis and Taggart model. The results of this study indicate that: (1) Learning or lectures with an online system in mathematics can be implemented by 83% or 5 points out of the 6 specified criteria have been implemented. (2) The effectiveness of learning mathematics using an online system after being held for 1 semester or 14 meetings obtained an average student score of 75.50 with a specified target of 70. This means that it is effective when viewed classically. (3) The effectiveness of learning mathematics using an online system after being held for 1 semester or 14 meetings, the number of students who completed it was 69% or from the specified target of 75%. This means that 31% of students are still incomplete, so it can be said that the online system for learning mathematics is not yet effective when viewed individually.